Foreign direct investment and pollution havens: evidence from African countries - GHARNIT, SAID; Bouzahzah, Mohamed; Ait Soussane, Jihad (Archives of Business Research, 2020)
This study examines the relationship between foreign direct investment (FDI) inflows and carbon dioxide emissions (CE) in order to investigate the validity of the pollution haven hypothesis for 54 African countries, using cointegration approach with dynamic panel data over the period 1960-2018. Based on the panel cointegration analysis, it was concluded that the variables are cointegrated. Moreover, the Dynamic Ordinary Least Square (DOLS) and Fully Modified Ordinary Least Square (FMOLS) results showed that foreign direct investment inflows have a long-run positive relationship with carbon dioxide emissions. Furthermore, according to Granger-Engle causality test results, FDI inflows and carbon dioxide emissions have a positive causal relationship, for both short-run and long-run. Thus, the results of this study validate the pollution haven hypothesis in the African countries. Nevertheless, it is recommended to keep attracting foreign direct investment inflows alongside of implementing mechanisms and instruments for reducing the CO2 emissions under strong environmental policies.